KANDUNGAN ACID DETERGENT FIBER, NEUTRAL DETERGENT FIBER DAN SELULOSA HIJAUAN Indigofera zollingeriana PADA JENIS TANAH YANG BERBEDA (The content of acid detergent fiber, neutral detergent fiber and sellulose Indigofera zollingeriana forage in..... - Amanda C. Lisu; Herayanti Panca Nastiti; Bernadete B. Koten (Universitas Nusa Cendana, 2022)
This study was carried out the Forage Field Laboratory of faculty Animal Husbandry at the University of Nusa Cendana, Kupang for 5 months (September 2019 to January 2020). The purpose this study was to assess the effect Indigofera zollingeriana planted in different soil types on Acid Detergent Fiber (ADF), Neutral Detergent Fiber (NDF) and Cellulose. The experiment was followed a Completely Randomized Design (CRC) with 3 treatments and 6 replications. The treatments were: P1= Alluvial soil, P2= renzina soil and P3= Latosol soil. The variables measured were ADF, NDF and Cellulose. Planting Indigofera zollingeriana in different soil types increased the NDF (P<0,05) content but had not significant effect (P>0,05) on ADF and cellulose content. It can be concluded that the NDF levels of Indigofera zollingeriana is determined by soil type Latosol produced the highest levels of NDF at 32,29%.